(untitled) (International Journal of Social Research & Innovation, 2018)
Cultures and Organizations: Software of the Mind is one of the most influential books on the study of cross-cultural management. This book includes the authors’ research findings conducted in more than seventy countries over a forty year span and helps us to examine how we think - and how we fail to think - as members of groups.